Isolation of Lacticaseibacillus rhamnosus SMHA30 from traditional yogurt: A probiotic with antimicrobial, anti-biofilm, and safety attributes - Behrooz Alizadeh Behbahani; Hassan Barzegar; Morteza Taki (Applied Food Research)
This study explored the probiotic potential, antimicrobial, safety, and anti-biofilm properties of Lacticaseibacillus rhamnosus SMHA30. The strain exhibited the highest cell viability at pH 4.5 (8.16 log colony forming unit (CFU)/mL) and the lowest at pH 2.5 (7.08 log CFU/mL). In bile stability tests, cell viability remained consistent across 0.30% and 0.50% bile concentrations (8.55 and 8.41 log CFU/mL). L. rhamnosus SMHA30 demonstrated a notable surface hydrophobicity of 57.61%, an auto-aggregation rate of 47.81%, and a co-aggregation rate of 50.50%, while adhering to Caco-2 cells at a rate of 12.95%. The strain effectively inhibited Listeria monocytogenes, with competition, inhibition, and displacement rates of 52.56%, 49.95%, and 24.95%, respectively. Furthermore, L. rhamnosus SMHA30 showed antioxidant activity with 2,2,-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-Azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) scavenging abilities of 53.60% and 61.43%, respectively, and demonstrated substantial anti-cancer effects on MCF-7, HeLa, and HT-29 cells. Additionally, the strain had a cholesterol assimilation rate of 52.95% and was resistant to ampicillin while being susceptible to other antibiotics. The strongest antibacterial effect was noted against L. monocytogenes, while the weakest was observed against Salmonella typhi. The minimum inhibitory concentration (MIC) was determined to be 7.81 mg/mL for L. monocytogenes and 125 mg/ mL for S. typhi. No biogenic amine production, DNase activity, or hemolysis was observed. In this research, Gaussian Process Regression (GPR) method was used to predict acid and bile tolerance. The results indicated that GPR can predict both the output parameters with high accuracy. Overall, L. rhamnosus SMHA30 represents a valuable candidate for further investigation in probiotic development and biofilm management strategies.